1998
DOI: 10.1002/(sici)1097-4547(19980901)53:5<521::aid-jnr2>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor induces chemotaxis of neuroepithelial stem cells

Abstract: The ability of differentiating cells to migrate within the developing central nervous system (CNS) depends on extrinsic guidance signals, some of which are growth factors. In this study we have investigated the chemotactic response of cultured stem cells from the embryonic rat cortex to platelet-derived growth factor (PDGF). Nestin-positive stem cells from the developing CNS can be maintained and expanded in vitro under serum-free conditions in the presence of basic fibroblast growth factor (bFGF). Northern bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…PDGFR␣ expression is found in neural stem cells and is a characteristic of this stem cell type (33,34). Expression of PDGFR␣ was observed in the isolated LHR-negative-PDGFR␣-positive cells, corroborating an increasing body of evidence that PDGF signaling is necessary for stem cell commitment and differentiation in the LC lineage of mice and neonatal rats (35,36).…”
Section: Discussionsupporting
confidence: 66%
“…PDGFR␣ expression is found in neural stem cells and is a characteristic of this stem cell type (33,34). Expression of PDGFR␣ was observed in the isolated LHR-negative-PDGFR␣-positive cells, corroborating an increasing body of evidence that PDGF signaling is necessary for stem cell commitment and differentiation in the LC lineage of mice and neonatal rats (35,36).…”
Section: Discussionsupporting
confidence: 66%
“…Although PDGF's role in smooth muscle cell, fibroblast, and oligodendrocyte migration is well established (Wolswijk et al 1991;Bilato et al 1995;Milner et al 1997;Facchiano et al 2000), its role in modulating astrocyte migration is less well defined and therefore merits further investigation. Indeed, cell culture studies have revealed the capacity of PDGF to stimulate migration of oligodendrocyte progenitor cells (Simpson and Armstrong 1999), neonatal rat cortical astrocytes (Bressler et al 1985), and embryonic rat neural stem cells (Forsberg-Nilsson et al 1998). In cell culture-based studies, PDGF, in combination with bFGF, has been shown to promote proliferation of glial progenitors and inhibit their terminal differentiation (McKinnon et al 1990).…”
Section: The Glioma-relevant Pathwaysmentioning
confidence: 99%
“…The discovery of netrins (18)(19)(20)(21), semaphorins (22)(23)(24), ephrins (25,26), and Slit proteins (27)(28)(29) established the existence of neuronal migration guidance signals at long distances by diffusible secreted proteins that have NSPC chemoattractant and repulsive properties. Recently it has been suggested that certain cytokines with known important functions in CNS development (i.e., transforming growth factor α, bFGF, and EGF) were capable of enhancing ischemia-induced progenitor proliferation and migration (30,31). Nevertheless, our understanding of the mechanisms guiding neural progenitor cell migration in pathological states remains limited.…”
Section: Introductionmentioning
confidence: 99%